PENGARUH JENIS PELARUT TERHADAP RENDEMEN DAN KARAKTERISTIK EKSTRAK PEWARNA DARI BUAH PANDAN (Pandanus tectorius) - Ratih Permata Sari, Ni Gst Ayu Kade; Wartini, Ni Made; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
The aimed of this research were to 1) know the influence of the type of solvent to yield and the characteristics of the resulting dye pandanus fruit. 2) get the best type of solvent that is able  to produce dye pandanus fruit. This study used a factorial randomized block design, which the treatment was the type of solvent consisting of 6 solvent, namely n-hexane, chloroform, ethyl acetate, acetone, ethanol, and water. The experiments are grouped into 3 groups based on the time of implementation, in order to obtain 18 units experiment. Samples were assayed byobjective and subjective to determine the best treatment. Objective variables observed that the yield, total carotenoids content, color intensity. Subjective variables observed that the level of color strength pandanus fruit extracts. The results showed that the type of solvent significantly affect on yield, levels of total carotenoids, strength of color, brightness (L*) andyellowish level (b*) dye pandanus fruit, but did not affect on redness level (a*). Solvent of chloroform was the best treatment to produce extract dye from pandanus fruit with the following characteristics: yield 2,43%; total carotenoid content 0,12%; brightness (L*) 8,01; yellowish level (b*) 40,07; and strength of color 4,5. Keyword :solvent, extraction, pandanus fruit, natural dyes
Keywords: 77